A framework for identifying the host phases in Coal-derived fly ash. (15th April 2022) - Mohebbi, Mina; Rajabipour, Farshad; Madadian, Edris
Highlights: A synergistic framework was developed to identify the main host phases in PC fly ash. QXRD identified the glass composition and the host phases for Si, Al, Fe, and Ca. SEM/EDS maps analysis detected the host phases for trace elements (As, B, Se, Mo). Column leaching test revealed the surface/interior association of elements. The Visual MINTEQ chemical model identified the formation/dissolution of host phases. Abstract: Harmful trace elements trapped in fly ash during coal combustion have the potential to be released to the environment. Characterizing the dominant host phases for environmentally important elements is necessary to control the impacts and develop sustainable industrial symbiosis. In this study, a synergistic framework including microcharacterization techniques and leaching tests was developed and assessed to identify the host phases in a pulverized coal fly ash. The Quantitative X-ray diffraction (QXRD) mainly identified the host phases for major elements (Al, Si, Ca, Fe), and characterized the glass phase oxide composition. Cluster analysis of elemental maps from scanning electron microscopy/ energy dispersive spectroscopy (SEM/EDS) was capable of effectively determining the host phases for trace elements (As, Mo, B, and Se). The results of column leaching tests detected the phases associated with surface (e.g., sodium- and potassium-sulfate salts) and those infused inside the glass matrix with delayed release. A geochemical model was built based on the QXRD and SEM/EDS results to analyze the leachate composition using minerals saturation indices and potential of sorption/desorption. A few host minerals for minor and trace elements such as carbonates for As and sulfide/organics for K were only detected by the sequential extraction method. By assessing the capabilities and limitations of selected techniques, the Integrating framework enabled identifying host phases for a wide range of major, minor, and trace elements in fly ash. Such methodology advances development of reactive transport models and predicting the long-term environmental impacts of combustion byproducts under various beneficial use scenarios.